3D imaging and quantification of porosity in electron beam welded dissimilar steel to Fe-Al alloy joints by X-ray tomography. (15th April 2016) - Dinda, Soumitra Kumar; Warnett, Jason M.; Williams, Mark A.; Roy, Gour Gopal; Srirangam, Prakash
Abstract: Dissimilar joining of mild steel and Fe-7% Al alloy was carried out using electron beam welding (EBW) process under three different weld operating conditions such as with beam oscillations, without beam oscillations and at higher welding speeds. Laboratory based X-ray computed tomography (XCT) was used for three dimensional (3D) visualisation of porosity under various welding conditions. Quantitative analysis of porosity such as the average size and number of pores were evaluated from XCT results as a function of beam oscillation and welding speed. XCT results show that the application of beam oscillation results in decrease in average size of the pores as well as a decrease in number of pores in the welded joints. Further, it was observed that an increase in weld speed results in an increase in porosity in the weld joint. Raman spectroscopy analysis shows the presence of hydrogen gas which could be responsible for porosity formation in EBW dissimilar joints. This study shows that the application of beam oscillation improves the weld quality by decreasing the porosity in the weld joints. Graphical abstract: Highlights: Dissimilar metals joining of steel and Fe-Al alloy by Electron Beam Welding (EBW). Lab source sub-micron resolution XCT was used for 3D visualisation and quantification of porosity in dissimilar joints. Application of beam oscillations decreases porosity formation in weld joints. Raman spectroscopy shows presence of hydrogen which could be the source of porosity in dissimilar joints.